2019
DOI: 10.1109/lawp.2018.2883235
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal to Improve Ray Launching Techniques

Abstract: In this study, we demonstrate the implementation of an algorithm to model 3D-ray launching. A fixed-size reception sphere and cylinder is used in conjunction with numerical methods to simulate the multipath propagation in a reduced computational time while retaining accuracy. This approach was implemented in a two office environments that were validated previously by the authors in different simulations. The mathematical feasibility of this method in these applications is demonstrated and the obtained results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…The data is fitted to a CI free-space model, also used in research previously reported as [ 40 , 42 ]. Further studies have been performed in order to analyze and enhance wireless channel operation, by analyzing interference impact, the use of deep learning techniques to optimize beam forming parameters or the proposal of new effective receiver volume configurations, among others [ 45 , 46 , 47 , 48 , 49 ].…”
Section: Related Workmentioning
confidence: 99%
“…The data is fitted to a CI free-space model, also used in research previously reported as [ 40 , 42 ]. Further studies have been performed in order to analyze and enhance wireless channel operation, by analyzing interference impact, the use of deep learning techniques to optimize beam forming parameters or the proposal of new effective receiver volume configurations, among others [ 45 , 46 , 47 , 48 , 49 ].…”
Section: Related Workmentioning
confidence: 99%
“…En los modelos de trazado de rayos, la predicción se basa en cálculos de transmisión y recepción de rayos en un espacio abierto, teniendo en cuenta principalmente el fenómeno de reflexión. Existen también modelos de trazado más completos que tienen en cuenta otro tipo de fenómenos como lo son, la difracción, dispersión difusa y penetración a través de materiales [8][9][10].…”
Section: Marco Teóricounclassified
“…When making this division, the wave fronts modify their size, but the relationship in shape and distance in the vicinity of the wave fronts is maintained. The number of rays launched by the transmitting source is given by [19]:…”
Section: Launch Algorithmmentioning
confidence: 99%
“…where N is the frequency of the division. The radial separation is a measure of the angular resolution of the scattering of the rays for ray launching [19] and was used to calculate the angular resolution of separation between the wave front neighborhood:…”
Section: Launch Algorithmmentioning
confidence: 99%
See 1 more Smart Citation